The library book (Simon & Schuster Audio, Audioworks, imprint of Simon & Schuster Audio, Thorndike Press, Simon and Schuster, Simon & Schuster, 2018)
Reopens the unsolved mystery of the most catastrophic library fire in American history, the 1986 Los Angeles Public Library fire, while exploring the crucial role that libraries play in modern American culture